SISTEM INFORMASI UNTUK BENGKEL RYN MANDIRI MOTOR DENGAN METODE BERBASIS AKRUAL - Edy Siswanto; Munifah Munifah; Dendy Kurniawan (Informatika: Jurnal Teknik Informatika dan Multimedia, 2024)
A well-organized system is essential for helping a company grow. With a properly managed system, activities such as services, sales, and purchases can run more smoothly. However, RYN Mandiri Motor Workshop still relies on manual methods, such as recording transactions with pen and paper or a calculator. This approach often takes a lot of time, is prone to errors, and hinders the management of finances and spare part inventory. Implementing an accrual-based accounting information system can be a solution to address these issues. This system will simplify transaction recording, inventory management, and financial reporting. In addition to speeding up and streamlining processes, it also enables the owner to monitor the company's financial condition and make more accurate decisions.